Strengthening Physics Scientific Literacy in the Millennial Generation through the Blended Learning Model - Amalia Aris, Nurul; Nurhandayani, Nurhandayani; Angraini, Nurvadillah; Rahmayani, Sitti; Masri, Mawardi Jalil (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study aims to analyze the improvement of scientific literacy in millennial students during physics learning through the implementation of the blended learning model. A quasi-experimental design with a nonequivalent control group was used. The experimental class applied the blended learning model, while the control class used conventional learning methods. Data were collected through scientific literacy tests administered as pretests and posttests, which were then analyzed using descriptive statistics and t-tests to examine the significance of differences between the two groups. The results indicate a significant difference in posttest scientific literacy scores between the experimental and control classes. The average posttest score in the experimental class was higher than that of the control class, suggesting that the blended learning model was more effective in enhancing students' scientific literacy. The t-test yielded a t-count of 2.053, which was greater than the t-table value of 1.996, with a significance level of 0.05. Based on these findings, it can be concluded that the blended learning model is more effective in improving the scientific literacy of millennial students, particularly in physics education. Future research could explore further optimization of blended learning implementation to enhance various aspects of scientific literacy.